Evaluation of the Reduction in Switching Time and Stress in Constant Electric Power Dependent Public Utilities by Automatic Mains and Phase Changer (International Journal of Engineering and Computer Science, 2014)
Power failure is the major factor that causes constant electric power-dependent public utilities to stop operation, making it paramount to have backup or alternative electric power sources to ensure the continuity of operation of these utilities. The power outage time lag experienced when these public utilities are switched from a failed electric power source to an available backup power source as well as the stress of manual switching, makes the operation of these utilities inefficient.The Automatic Mains and Phase Changer (AMPC) is a device that aids in greatly reducing the power outage time lag during the switching between power sources. It also eliminates the stress of manually switching between power sources.This paper reports a research that evaluates the relationship between the time lag experienced with the use of the AMPC and the time lag experienced when the switching is done manually. It also evaluates the relationship between the stress levels during manual load switching and the stress levels using the AMPC for automatic load switching.The research involved the use of an Automatic Mains and Phase Changer to provide automatic switching from a failed phase of the mains supply to an available phase of the same mains supply. The time lag in the automatic switching was compared with the time lag experienced when the same switching process was done manually. With the load being a single phase load, it can be switched between the phases of a 3-phase mains supply depending on which phase is available.The research also involved the use of the AMPC to provide automatic switching from a mains power supply to a generator supply. The time-lag in the automatic switching using AMPC was compared with the time-lag when the switching was done manually and the relationship between the time-lags was fully analyzed and evaluated in this paper. 20 different time-lag readings were taken with the AMPC used and with the switching done manually and the analysis of the relationship between the time-lags as well as the relationship between the stress levels of both, is well documented in this paper. The result of this research showed that change-over time is greatly reduced with the AMPC, compared to manual change-over time which depends on the position of the operator relative to the position of the change-over switch.